Computed tomography as an aid to planning intubation in the difficult airway. Issue 1 (January 2016) - Grimes, David; MacLeod, Iain; Taylor, Timothy; O'Connor, Mary; Sidebottom, Andrew
Abstract: Patients having oral and maxillofacial operations often require nasal intubation, but limited mouth opening and unfavourable nasal anatomy can make it difficult. We aimed to find out whether there is an association between the prediction of difficult nasal intubation on computed tomography (CT) and actual problems. We retrospectively reviewed the imaging and anaesthetic records of 77 patients who had replacement of the temporomandibular joint (TMJ) as these patients often have limited mouth opening and have had a preoperative CT. There was a positive correlation between a radiographically-assessed difficult nostril and difficulty of intubation (p<0.001). The positive predictive value was 71.4%. As a consequence, our radiologists now routinely report on the nasal cavity in these patients, and their report and the scan are then reviewed by the anaesthetist before intubation. Our results suggest that review of the CT before planned nasal intubation should be part of routine practice.